Determination of Trophic Structure in Selected Freshwater Ecosystems by using Stable Isotope Analysis - Amila Faqhira Zainordin; Suhaila Ab Hamid (Tropical Life Sciences Research, 2017)
Stable isotope analysis has been used extensively to establish trophic relationships in many ecosystems. Present study utilised stable isotope signatures of carbon and nitrogen to identify trophic structure of aquatic food web in river and rice field ecosystems in Perak, northern peninsular Malaysia. The mean ?13C values of all producers ranged from - 35.29 ± 0.21 to - 26.00 ± 0.050 ‰. The greatest ?15N values noted was in zenarchopterid fish with 9.68 ± 0.020 ‰. The ?15N values of aquatic insects ranged between 2.59 ± 0.107 in Elmidae (Coleoptera) and 8.11 ± 0.022 ‰ in Nepidae (Hemiptera). Correspondingly, with all the ?13C and ?15N values recorded, it can be deduced that there are four trophic levels existed in the freshwater ecosystems which started with the producer (plants), followed by primary consumer (aquatic insects and non-predatory fish), secondary consumer (invertebrate predators) and lastly tertiary consumer (vertebrate predators). Analisis isotop stabil telah digunakan secara meluas untuk mewujudkan hubungan trofik dalam pelbagai ekosistem. Kajian ini menggunakan tanda isotop stabil karbon dan nitrogen untuk mengenal pasti jaringan makanan akuatik dalam ekosistem sungai dan sawah padi di Perak, utara Semenanjung Malaysia, dan juga untuk menentukan struktur trofik jaringan makanan yang telah dikenal pasti. Nilai min ?13C untuk semua pengeluar berjulat dari - 35.29 ± 0.21 hingga - 26.00 ± 0.050 ‰. Nilai ?15N yang terbesar terdapat dalam ikan zenarchopterid dengan 9.68 ± 0.020 ‰. Nilai ?15N serangga akuatik berjulat antara 2.59 ± 0.107 dalam Elmidae (Coleoptera) dan 8.11 ± 0.022 ‰ dalam Nepidae (Hemiptera). Sehubungan dengan itu, dengan semua nilai ?13C dan ?15N yang telah direkod, ia boleh disimpulkan bahawa terdapat empat tahap trofik yang wujud dalam ekosistem air tawar yang bermula dengan pengeluar (tumbuh-tumbuhan), diikuti oleh konsumer primer (serangga akuatik dan ikan bukan pemangsa), konsumer sekunder (pemangsa invertebrata) dan akhir sekali konsumer tertier (pemangsa vertebrata).